Success Rate for Immidate & Delayed Loading Protocols - Karuna Gajanan Pawashe (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Implant placement can be done by following IL & DLP . ISQ value is used to assess stability at implant -tissue interface to assess the difference between sucess and failure. Aim: To compare & evaluate the SR in DI loaded with IL and DLP. Materials & method: An invivo study with 34 patients were divided in 2 groups i.e. IL & DL were assessed for MBL& ISQ at different time interval i.e.( baseline, 3rd month, 6th month and 9th month) at both the proximal sides. Result: A significant difference seen at different follow-ups for MBL while insignificant for ISQ value for both the groups. Conclusion: More studies are recommended in future.